THE EFFECT OF LEADERSHIP STYLE ON THE EMPLOYEE’S PASSION AT THE BUREAU FINANCIAL AND STATE ASSETS INVENTORY THE DEPARTMENT OF RELIGION THE REPUBLIC OF INDONESIA - Syahrian, Syahrian (Dinasti Publisher, 2019)
The purpose of this paper is to assess the ability of writers, especially in understanding the knowledge and knowledge gained and apply it in practice, so that later it can help the writer to convey, use, apply knowledge and knowledge that has been able to overcome the problem of leadership style on employee passion in Bureau of Financial and State Assets Inventory Department of Religion the Republic of Indonesia. This research authors compile based on scientific methods, using descriptive methods, namely by collecting data and providing a clear picture. This data was obtained through field research, questionnaire questionnaires, literature and statistical analysis to prove the results that have been studied. Based on the description and discussion of the influence of leadership style on employee passion, the writer can conclude that there is a strong influence relationship between leadership style on employee passion at the Financial Bureau and the State Assets Inventory of the Department of Religion the Republic of Indonesia.